2018
DOI: 10.1016/j.cub.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Fur Seals Suppress REM Sleep for Very Long Periods without Subsequent Rebound

Abstract: Virtually all land mammals and birds have two sleep states: slow-wave sleep (SWS) and rapid eye movement (REM) sleep [1, 2]. After deprivation of REM sleep by repeated awakenings, mammals increase REM sleep time [3], supporting the idea that REM sleep is homeostatically regulated. Some evidence suggests that periods of REM sleep deprivation for a week or more cause physiological dysfunction and eventual death [4, 5]. However, separating the effects of REM sleep loss from the stress of repeated awakening is dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 38 publications
2
70
0
Order By: Relevance
“…) and even fur seal (Lyamin et al . ) (though some monkey studies reported just the opposite (Reite & Pegram, ; Hayward & Baker, )). It is debated whether this effect is aimed to protect brain function from REM‐associated hypothermia, or simply reflects the increased metabolic activity due to increased unit firing.…”
Section: Discussionmentioning
confidence: 96%
“…) and even fur seal (Lyamin et al . ) (though some monkey studies reported just the opposite (Reite & Pegram, ; Hayward & Baker, )). It is debated whether this effect is aimed to protect brain function from REM‐associated hypothermia, or simply reflects the increased metabolic activity due to increased unit firing.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, a study in mice reported remarkable differences across phasic and tonic REM states with respect to theta and gamma oscillations in the parietal cortex of the animals [134]. Exploring the distribution of, and neural (i.e., frequency-specific) activity during phasic and tonic REM periods in species exhibiting peculiar forms of sleep due to environmental constraints [8], or in species outside the mammalian order [2,135] could shed more light on the functions and evolutionary origins of REM sleep [136,137].…”
Section: Conclusion Open Questions and Future Directionsmentioning
confidence: 99%
“…Indeed, empirical data indicates that REM-related muscle twitches contribute to the development of the sensorimotor system [6,7]. In addition, REM sleep functions putatively encompass a wide range of neural and cognitive phenomena from basic mechanisms such as the regulation of brain temperature [8], modulation of receptor sensitivity [9], and synaptic plasticity [10], to more complex processes such as procedural [11] and declarative [12] learning, emotional memory processing [13,14], or the development of consciousness [15].…”
mentioning
confidence: 99%
“…However, recent work using EEG recordings from the great frigatebird Fregata minor showed that these birds, which can maintain flight for up to 10 days, accomplish in‐flight sleep through both unihemispheric and bihemispheric sleep, but that the duration of this sleep is less than 10% of their normal sleep time on land (Rattenborg et al., ). Interestingly, the fur seal, which lives both on land and in seawater, suppresses slow wave sleep when in the water and shows no subsequent slow wave rebound upon returning to land (Lyamin et al., ). Taken together, these examples indicate that certain ecological conditions can drive context‐dependent sleep suppression; however, it remains unclear if or how these animals might upregulate other processes to compensate for lost sleep.…”
Section: The Universality Of Sleepmentioning
confidence: 99%